PEMANFAATAN MEDIA PEMBELAJARAN BERBASIS AUGMENTED REALITY UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR SISWA - Neliwati; Irfan; Fira Dwi Putri; Muliana Putri; Abdi Syahputra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to explore how the use of Augmented Reality (AR)–based learning media can enhance students’ learning motivation and learning outcomes. Using a qualitative approach, the research examines students’ experiences, perceptions, and responses to the implementation of AR media in the learning process. Data were collected through in-depth interviews, participatory observation, and documentation studies involving secondary school students who used AR-based learning media for one semester. Data analysis was conducted thematically to identify patterns of change in students’ motivation and learning achievement. The findings indicate that AR-based learning media provide more engaging and interactive learning experiences, thereby increasing students’ intrinsic motivation. Furthermore, the use of AR media facilitates a better understanding of concepts, which is reflected in a significant improvement in learning outcomes. This study recommends broader integration of AR media in learning as an innovative strategy to improve the quality of education.